Franz von Ottenthal (1818-1899) Arzt und Tiroler Landtagsabgeordneter - Taddei, Elena (2010)
Dr. Franz von Ottenthal served as a General Practitioner in Sand, in the South Tyrolean Tauferer Ahrntal from 1847 to 1899, over a period lasting more than 50 years. From 1861 until 1882, in a period of great regional and imperial tensions, he even was member of the Tyrolean Landtag (diet). In 1837/8 he began his medical studies at the University of Vienna, where important physicians from the "Zweite Wiener Medizinische Schule" like Carl von Rokitansky, Joseph Skoda and Philipp Semmelweis were teaching. Ottenthal worked as a medical expert in Windisch-Matrei (East Tyrol) for almost two years. Then he went back home and became a General Practitioner in Neumelans, the residence of his family. This biography treats particularly the career as a physician, his engagement in the medical service and the difficulties during the collaboration with medical authorities. On the other side it contains further an analysis of the medical records and the letters of his patients for a better patient view. Further this biography discusses open questions like medical development, fees, properties of a noble rural physicians in the second part of the 19 century and the competition with other physicians and healers. A big space is dedicated to the treatment of mental illness. Ottenthal wasn't a 'psychiatrist', but he was as well responsible for the care and the treatment of persons with mental disease. With a report by a physician began - crossing a lot of other institutions - the way in the asylum. The Ottenthal family, whose everyday life has tried to be reconstructed along private correspondence, is a typical example of a family from the second part of the 19th century between nobility and bourgeoisie characterized on the one hand by qualification, know-how and a lucrative job and on the other by a nobility title, fortune and landed property. Franz von Ottenthal wasn't a famous physician like Rudolf Virchow, Robert Koch or Carl von Rokitansky. Nevertheless he was a modern, political engaged, self-confident practitioner and he is a very good example for the fusion of nobility and bourgeoisie in a rural life of the 19th century. This publication should be a contribution to the exploration of rural medical practice, which is little known and often poor of sources. It will even be a starting-point for further comparative studies of other medical biographies and legacies.